Rapamycin, by Inhibiting mTORC1 Signaling, Prevents the Loss of Striatal Bidirectional Synaptic Plasticity in a Rat Model of L-DOPA-Induced Dyskinesia - Calabrese, Valeria; Di Maio, Anna; Marino, Gioia; Cardinale, Antonella; Natale, Giuseppina; De Rosa, Arianna; Campanelli, Federica; Mancini, Maria; Napolitano, Francesco; Avallone, Luigi; Calabresi, Paolo; Usiello, Alessandro; et al. (Frontiers in aging neuroscience, 2020)
Levodopa (L-DOPA) treatment is the main gold-standard therapy for Parkinson’s disease (PD). Besides good antiparkinsonian effects, prolonged use of this drug is associated to the development of involuntary movements known as L-DOPA-induced dyskinesia (LID). LID is linked to a sensitization of dopamine (DA) D1 receptors located on spiny projection neurons (SPNs) of the dorsal striatum. Several evidences have shown that the emergence of LID can be related to striatal D1/cAMP/PKA/DARPP-32 and extracellular signal-regulated kinases (ERK1/2) pathway overactivation associated to aberrant N-methyl-D-aspartate (NMDA) receptor function. In addition, within striatum, ERK1/2 is also able to modulate in a D1R-dependent manner the activity of the mammalian target of Rapamycin complex 1 (mTORC1) pathway under DA depletion and L-DOPA therapy. Consistently, increased mTORC1 signaling appears during chronic administration of L-DOPA and shows a high correlation with the severity of dyskinesia. Furthermore, the abnormal activation of the D1/PKA/DARPP-32 cascade is paralleled by increased phosphorylation of the GluA1 subunit of the AMPA receptor at the PKA Ser845 site. The GluA1 promotes excitatory AMPA receptor-mediated transmission and may be implicated in the alterations found at the corticostriatal synapses of dyskinetic animals. In our study, we investigated the role of mTORC1 pathway activation in modulating bidirectional striatal synaptic plasticity in L-DOPA treated parkinsonian rats. Inhibition of mTORC1 by co-administration of Rapamycin to L-DOPA, was able to limit the magnitude of LID expression, accounting for a therapeutic effect of this drug. In particular, behavioral data showed that in L-DOPA-treated rats, Rapamycin administration induced a selective decrease of distinct components of abnormal involuntary movements (i.e. axial and orolingual dyskinesia). Furthermore, ex vivo patch clamp and intracellular recordings of SPNs revealed that pharmacological inhibition of mTORC1 also resulted associated to a physiological bidirectional plasticity, when compared to dyskinetic rats treated with L-DOPA alone. This study uncovers the important role of mTORC1 inhibition to prevent the loss of striatal bidirectional plasticity under chronic L-DOPA treatment in rodent models of PD.